Identifikasi Gaya Belajar Peserta Didik Berdasarkan Teori Multiple Intelligences - Yasher, Surya; Ahmad, Faqih Sultan; Faizi, Muhammad Rafa; Rohmah, Meisya Maulidina; Lestari, Ananda; Sholihah, Lintang Al-Mar’atus; Artauli, Anastasia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
The This study aims to identify dominant multiple intelligence profiles among learners aged 16 to 29 years and to analyze their implications for determining learning style preferences. A quantitative descriptive survey design was employed using purposive sampling, resulting in a sample of 20 respondents. Data were collected online with a validated Multiple Intelligence Profile Questionnaire in a four point Likert format. Data analysis included descriptive statistics to map the distribution of intelligences and correlation analysis to examine the relationship between dominant intelligences and preferred learning styles. Findings indicate a clear association between dominant intelligence types and the learning styles selected by participants, suggesting that MI profiles can inform more adaptive instructional design such as using visual media for spatial learners and hands on activities for kinesthetic learners. The results have implications for curriculum planning and learner centered teaching design. Future research should expand sample size, adopt probabilistic sampling, and implement intervention studies to quantify the impact of MI based instructional adjustments on learning outcomes.